Biological Sex Is Binary and Rooted in Anisogamy - Tim Janicke; Göran Arnqvist; Pierre‐André Crochet; Patrice David; Philippe Jarne; Jussi Lehtonen; Thomas Lenormand; Edward H. Morrow; Geoff A. Parker; Paul A. Saunders; Jeanne Tonnabel; Frédéric Veyrunes; et al. (Ecology Letters, 2026)
The definition of biological sex has become a renewed focus of societal debate, fuelled by the conflation of biological principles with discussions of human gender diversity. Here, we argue that conceptual clarity critically depends on separating these domains. Drawing on evolutionary theory and empirical evidence, we maintain that biological sex is best defined as a binary classification of male and female reproductive strategies rooted in anisogamy, characterised by the production of two discrete gamete types of different sizes. We stress that gamete size constitutes the ultimate criterion for biological sex and that this definition applies consistently across sexual systems, from separate‐sexed species to hermaphrodites, irrespective of variation in karyotype, hormonal profile, somatic phenotype, or behaviour. Further, we emphasise that evolutionary insights offer a coherent explanation for recurring, though not universal, associations between biological sex and patterns of sex‐specific selection, sexual dimorphism and parental care. We conclude that the definition of biological sex as a binary classification based on gamete size is a powerful scientific framework compatible with the diversity of sexual phenotypes found in anisogamous organisms and distinct from the concept of human gender.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Substantiating chemical groups for read-across using molecular response profiles - Rosemary E. Barnett; Thomas N. Lawson; Claudia Rivetti; Carlos Barata; Mark T.D. Cronin; Silvia Lacorte; Gavin R. Lloyd; Ralf J.M. Weber; Matthew J. Smith; Andrew D. Southam; Adam Biales; Kara Koehrn; et al. (Regulatory Toxicology and Pharmacology, 2025)

Restoring functional farmland biodiversity for biological pest control - Kris A.G. Wyckhuys; Kathryn Bushley; Claudio Gratton; Geoff M. Gurr; Gabor Pozsgai; Teja Tscharntke; Thomas C. Wanger; Yanhui Lu; Maged Elkahky (Trends in Plant Science, 2025)

Integrated modeling of nature’s role in human well-being: A research agenda - Rebecca Chaplin-Kramer; Stephen Polasky; Rob Alkemade; Neil D. Burgess; William W.L. Cheung; Ingo Fetzer; Mike Harfoot; Thomas W. Hertel; Samantha L.L. Hill; Justin Andrew Johnson; Jan H. Janse; Patrick José v. Jeetze; et al. (Global Environmental Change, 2024)

Opportunities to reduce energy consumption and CO₂ emissions from ironmaking blast furnace using CO₂ electrolysis to CO for carbon recycling - Yichao Hu; Thomas E. Rufford; Jian Chen; Liangyuan Hao; Mengran Li; Yinxuan Qiu; Sahil Garg; Victor Rudolph; Geoff Wang (Journal of Cleaner Production, 2023)

Uncertainty of Gridded Precipitation at Local and Continent Scales: A Direct Comparison of Rainfall from SILO and AWAP in Australia - Guobin Fu; Olga Barron; Stephen P. Charles; Michael J. Donn; Thomas G. Van Niel; Geoff Hodgson (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Hidden diversity of Macrophomina associated with broadacre and horticultural crops in Australia - Barsha Poudel; Roger G. Shivas; Dante L. Adorada; Martin J. Barbetti; Sean L. Bithell; Lisa A. Kelly; Natalie Moore; Adam H. Sparks; Yu Pei Tan; Geoff Thomas; Joop Van Leur; Niloofar Vaghefi (European Journal of Plant Pathology, 2021)

The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation - Richard Christopher Chiverrell; Geoff Stephen Powell Thomas; Matthew Burke; Alicia Medialdea; Rachel Smedley; Mark Bateman; Chris Clark; Geoffrey A. T. Duller; Derek Fabel; Geraint Jenkins; Xianjiao Ou; Helen Marie Roberts; et al. (Journal of Quaternary Science, 2021)
Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.

Global transcriptomic profiles of circulating leucocytes in early lactation cows with clinical or subclinical mastitis - Zhangrui Cheng; Laura Buggiotti; Mazdak Salavati; Cinzia Marchitelli; Sergio Palma-Vera; Alistair Wylie; Haruko Takeda; Lijing Tang; Mark A. Crowe; D. Claire Wathes; Mark Crowe; Niamh McLoughlin; et al. (Molecular Biology Reports, 2021)

Multi-locus phylogeny and pathogenicity of Stemphylium species associated with legumes in Australia - Niloofar Vaghefi; Susan M. Thompson; Rohan B. E. Kimber; Geoff J. Thomas; Pragya Kant; Martin J. Barbetti; Joop A. G. van Leur (Mycological Progress, 2020)

Evidence for a 200 km thick diamond-bearing root beneath the Central Mackenzie Valley, Northwest Territories, Canada? Diamond indicator mineral geochemistry from the Horn Plateau and Trout Lake regions - Stéphane P. Poitras; D. Graham Pearson; Matthew F. Hardman; Thomas Stachel; Geoff M. Nowell; Scott Cairns (Mineralogy and Petrology, 2018)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Mutant strains of Pichia pastoris with enhanced secretion of recombinant proteins - Sasha Larsen; Jun Weaver; Katherine de Sa Campos; Rhobe Bulahan; Jackson Nguyen; Heather Grove; Amy Huang; Lauren Low; Namphuong Tran; Seth Gomez; Jennifer Yau; Thomas Ilustrisimo; et al. (Biotechnology Letters, 2013)

Crown structure and vertical foliage distribution in 4-year-old plantation-grown Eucalyptus pilularis and Eucalyptus cloeziana - Philip J. Alcorn; David I. Forrester; R. Geoff B. Smith; Dane S. Thomas; Ryde N. James; Adrienne B. Nicotra; Jürgen Bauhus (Trees, 2013)

Application of meta-analysis in plant pathology: a case study examining the impact of fungicides on wheat yield loss from the yellow spot—septoria nodorum blotch disease complex in Western Australia - Kawsar P. Salam; Geoff J. Thomas; Ciara Beard; Robert Loughman; William J. MacLeod; Moin U. Salam (Food Security, 2013)

Fine‐scale regional climate patterns in the Guianas, tropical South America, based on observations and reanalysis data - C. Isabella Bovolo; Ryan Pereira; Geoff Parkin; Chris Kilsby; Thomas Wagner (International Journal of Climatology, 2012)
The dense, intact rainforests of the Guianas (northern Amazonia) are important for the regulation of the local and regional climate, but preclude easy access so a large data gap exists. The rainforest–savannah boundary may also be particularly susceptible to increasing pressures from ecosystem exploitation and climate change. It is important therefore to establish a baseline climate regime so that the impacts of any future change can be determined. Currently this area is not covered by the publicly available climate data sets, so interpolated data sets are not an accurate representation of the climate of this area, emphasizing the need for a more detailed analysis in this region. Here, we collate the available data sets and use these to derive maps of observed precipitation and temperature across the region. To overcome the limitations in the inadequate observational data sets, we also test and use the ECMWF ERA‐40 reanalysis data set for the period 1958–2001 at a ∼125 km 2 (1.125°) resolution. Mean differences (biases) and annual average spatial correlations are examined between modelled and observed time series comparing the seasonal cycles and the yearly, monthly and monthly anomaly time series. The results show that with the exception of sub‐grid resolution mountain environments, reanalysis data for the Guianas provide a consistent and relatively accurate spatial distribution of temperature. Precipitation is modelled less accurately, with best results for the average timings, length and severity of the dry periods. This study provides consistent and quantitative details on the spatial variations in seasonality, particularly in areas lacking observations, thereby advancing beyond previous studies. Precipitation is highly variable in the region so care must be taken when averaging modelled data over large geographical areas for comparisons with gridded data sets based on few observations. This is the first comprehensive study of the recent historical climate and its variability in this area. Copyright © 2011 The Authors. Journal compilation © 2011 The Royal Meteorological Society

Adapting to climate change through local municipal planning: barriers and challenges - Thomas G. Measham; Benjamin L. Preston; Timothy F. Smith; Cassandra Brooke; Russell Gorddard; Geoff Withycombe; Craig Morrison (Mitigation and Adaptation Strategies for Global Change, 2011)

Advances in winter pulse pathology research in Australia - Moin U. Salam; Jennifer A. Davidson; Geoff J. Thomas; Rebecca Ford; Roger A. C. Jones; Kurt D. Lindbeck; William J. MacLeod; Rohan B. E. Kimber; Jean Galloway; Nitin Mantri; Joop A. G. van Leur; Brenda A. Coutts; et al. (Australasian Plant Pathology, 2011)

Nursery transplant practices determine seedling root quality of two subtropical eucalypts - Dane S. Thomas; Geoff A. Heagney; Piers Harper (New Forests, 2008)

Reducing airborne ectomycorrhizal fungi and growing non-mycorrhizal loblolly pine (Pinus taeda L.) seedlings in a greenhouse - Aaron D. Stottlemyer; G. Geoff Wang; Christina E. Wells; David W. Stottlemyer; Thomas A. Waldrop (Mycorrhiza, 2008)

ACMT position statement: Institutions housing venomous animals - Steven A. Seifert; Dan Keyler; Geoff Isbister; Jude McNally; Thomas G. Martin (Journal of Medical Toxicology, 2006)

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.

Quantification and cellular localization of dopamine in the salivary gland of the ixodid tick Amblyomma hebraeum - W. Reuben Kaufman; B. Duff Sloley; Roger J. Tatchell; Geoff L. Zbitnew; Thomas J. Diefenbach; Jeffrey I. Goldberg (Experimental and Applied Acarology, 1999)